The Effect of Profitability, Leverage, Liquidity, Free Cash Flow on Company Value with Dividend Policy as Moderating in Basic and Chemical Industrial Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period - Sinaga, Sara Herda Krisna; Azhar Maksum; Sirojuzilam (International Journal of Economics (IJEC), 2022)
This study aims to examine and analyze the effect of Profitability, Leverage, Liquidity and Free Cash Flow on Firm Value with Dividend Policy as a Moderating Variable. The population in this study were 66 companies in the Basic Industry and Chemical Sector which were listed on the Indonesia Stock Exchange (IDX) for the period 2017 - 2021, using a purposive sampling technique so that 61 samples were obtained for 5 years with a total of 305 observational data. Methods of data analysis using panel data regression analysis with the help of the Eviews application program. The results of the study show that partially Profitability, Leverage, Liquidity and Free Cash Flow have a positive and significant impact on Firm Value. Meanwhile, Dividend Policy as a moderating variable is unable to moderate the effect of Profitability, Leverage, Liquidity and Free Cash Flow on Firm Value.